Two-Photon Excited Fluorescence Lifetime Imaging of Tetracycline-Labeled Retinal Calcification - Kavita R. Hegde; Krishanu Ray; Henryk Szmacinski; Sharon Sorto; Adam C. Puche; Imre Lengyel; Richard B. Thompson (Sensors, 2023)
Deposition of calcium-containing minerals such as hydroxyapatite and whitlockite in the subretinal pigment epithelial (sub-RPE) space of the retina is linked to the development of and progression to the end-stage of age-related macular degeneration (AMD). AMD is the most common eye disease causing blindness amongst the elderly in developed countries; early diagnosis is desirable, particularly to begin treatment where available. Calcification in the sub-RPE space is also directly linked to other diseases such as Pseudoxanthoma elasticum (PXE). We found that these mineral deposits could be imaged by fluorescence using tetracycline antibiotics as specific stains. Binding of tetracyclines to the minerals was accompanied by increases in fluorescence intensity and fluorescence lifetime. The lifetimes for tetracyclines differed substantially from the known background lifetime of the existing natural retinal fluorophores, suggesting that calcification could be visualized by lifetime imaging. However, the excitation wavelengths used to excite these lifetime changes were generally shorter than those approved for retinal imaging. Here, we show that tetracycline-stained drusen in post mortem human retinas may be imaged by fluorescence lifetime contrast using multiphoton (infrared) excitation. For this pilot study, ten eyes from six anonymous deceased donors (3 female, 3 male, mean age 83.7 years, range 79–97 years) were obtained with informed consent from the Maryland State Anatomy Board with ethical oversight and approval by the Institutional Review Board.